Determinats Of The Amount Of Related Party Transaction: Tax Expense And Institutional Ownership - Lia Rahmawati Soraya; Nurul Aisyah Rachmawati (Universitas Muhammadiyah Malang, 2021)
This research is testing whether tax expense and institutional ownership have an influence on the amount of Related Party Transactions (RPT) both related to sales and expense (RPTSE). The population in this research is manufacturing companies listed on the Indonesia Stock Exchange with a total sample of 174 out of 58 manufacturing companies with research period in 2016-2018. By using panel data regression analysis, the results showed indicate that the tax expense of the previous year has a significant positive effect on the amount of related party transactions related to sales and expenses (RPTSE). This shows that the tax expense can encourage companies to conduct related party transactions in the following year. Meanwhile, institutional variables do not have a significant effect on related party transactions related to sales and expense (RPTSE).Practically, related party transactions are relatively complex, so that institutional ownership does not guarantee tomonitor of these transactions.